Detection of Environmental Sources of Histoplasma capsulatum in Chiang Mai, Thailand, by Nested PCR - Treepradab Norkaew (2018)
Histoplasmosis is a systemic mycosis caused by inhaling spores of Histoplasma capsulatum, a dimorphic fungus. This fungus grows in soil contaminated with bat and avian excreta. Each year, patients with disseminated histoplasmosis have been diagnosed in Chiang Mai, northern Thailand. No published information is currently available on the environmental sources of this fungus in Chiang Mai or anywhere else in Thailand. The aim of this study was to detect H. capsulatum in soil samples contaminated with bat guano and avian droppings by nested PCR. Two hundred and sixty-five samples were collected from the following three sources: soil contaminated with bat guano, 88 samples; soil contaminated with bird droppings, 86 samples; and soil contaminated with chicken droppings, 91 samples. Genomic DNA was directly extracted from each sample, and H. capsulatum was detected by nested PCR using a primer set specific to a gene encoding 100-kDa-like protein (HcI, HcII and HcIII, HcIV). Histoplasma capsulatum was detected in seven of 88 soil samples contaminated with bat guano, one of 21 soil samples contaminated with pigeon droppings and 10 of 91 soil samples contaminated with chicken droppings. The results indicate the possibility of the association of bat guano and chicken droppings with H. capsulatum in this area of Thailand. © 2013 Springer Science+Business Media Dordrecht.